PERBANDINGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA - Maslahah Maslahah; Rica Rica Wijayanti; Nur Aini (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
This study aims to describe student learning outcomes taught using the Problem Based Learning and Discovery Learning learning model and compare student learning outcomes taught using the Problem Based Learning learning model and the Discovery Learning learning model. Research uses experiments of quantitative methods with research design using the actual experimental design (true-ed) with the form of the design of the control group only post-test. The results of the study show that the value is sig. (2-tailed) is 0.045 or smaller than 0.05 meaning rejected and accepted which means comparison of student learning outcomes taught using the Problem Based Learning learning model and the Discovery Learning learning model is not the same. The conclusion of this study is the average learning outcomes of students using the Problem Based Learning learning model of 63.5, the average learning outcomes of students use the Discovery Learning learning model of 49.2, the average student learning outcomes use the BAS problem learning model